Business Model Design Based on Blue Ocean Strategy Based for Eco-Friendly Sativa Mouthwash - Luzi Zafriana; Prihono (UNIPA PRESS, 2023)
Sativa mouthwash based on 3% nigella sativa extract contains thymoquinone which can reduce the porphyromonas gingivalis bacteria that causes gingivitis and bad breath. Based on the inhibition zone test it can reduce the E faecalis bacteria that causes cavities. Oral hygiene and health have a broad impact on the condition of the immune system of all organs of the human body. Such a great opportunity for the development of the world of health, it is necessary to develop a business strategy for Sativa mouthwash products through the Business Model Canvas and its blue ocean strategy. Problems that often occur to consumers with a tropical climate in Indonesia are oral health problems and concerns about product safety for the health of other organs. This research method uses descriptive analysis with case studies on Sativa brand mouthwash products. The results of the SWOT analysis are in quadrant I (1.610928; 2.326923), indicating that there are still many strengths and opportunities for the development of the Sativa mouthwash product business. Progressive action is needed through the redesign of the Business Model Canvas, followed by the preparation of the Blue Ocean Strategic using a four-step framework, including no longer using unprofessional key partners, reducing waste in the production and distribution process, increasing value propositions, and creating a unique and attractive web for educating community about the importance of oral health and the importance of using mouthwash that is safe and eco-friendly.